2021
DOI: 10.1111/tbj.14198
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoma of the breast: A clinicopathologic analysis of 51 cases with a specific emphasis on patients with a history of breast carcinoma

Abstract: Breast lymphoma (BL) is a rare entity representing 1%-2% of breast malignancies while being the most common extra-mammary cancer involving the breast. It primarily affects postmenopausal women with a similar clinical presentation as breast carcinoma. It is classified into two main categories: primary breast lymphoma (PBL), and secondary breast lymphoma (SBL) as part of systemic disease. Bilateral breast involvement is not an uncommon situation and was reported in 0%-25% of patients with PBL in the previous ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…No marked difference was observed between primary and secondary breast involvement of hematological malignancies except that bilaterality was only seen in secondary involvement. Similar to these findings, Genco et al also reported no significant difference between patients with primary and secondary breast lymphoma [7]. The most common presenting symptoms were neck and axillary masses before breast involvement in the cases with secondary diseases, while the patients with primary breast lymphoma did not have any symptoms except breast or axillary masses.…”
Section: Discussionsupporting
confidence: 52%
“…No marked difference was observed between primary and secondary breast involvement of hematological malignancies except that bilaterality was only seen in secondary involvement. Similar to these findings, Genco et al also reported no significant difference between patients with primary and secondary breast lymphoma [7]. The most common presenting symptoms were neck and axillary masses before breast involvement in the cases with secondary diseases, while the patients with primary breast lymphoma did not have any symptoms except breast or axillary masses.…”
Section: Discussionsupporting
confidence: 52%
“…Average age of the cases was 59.13 years, while there was only one male among the 32 patients in this study, that was similar to Genco et al’s study. 7 Our results indicated that the 5-year PFS in patients with DLBCL of the breast was 44% and the OS was 49%. This study also showed that 5 year survival time was not related to age, tumour site, tumour size, IPI score, B symptoms, pathological origin, metastasis, comorbidities, or IR.…”
Section: Discussionmentioning
confidence: 54%
“…One possible example is that of Mucosa-associated lymphoid tissue (MALT) lymphomas that originate in sites of chronic epithelial inflammation in various sites of the body, where it plays a role in regulating mucosal immunity [41]. MALT lymphomas are present in the gastrointestinal tract [42], nasopharynx [43], thyroid [44], breast [45], lung [46], salivary glands [47], eye [48], and skin [49] and exhibit characteristics with B cells located in the marginal zone of lymph node follicles. MALT lymphomas originate in sites of chronic epithelial inflammation.…”
Section: Discussionmentioning
confidence: 99%